2021
DOI: 10.3390/cells10082103
|View full text |Cite
|
Sign up to set email alerts
|

Role of Irisin in Myocardial Infarction, Heart Failure, and Cardiac Hypertrophy

Abstract: Irisin is a myokine derived from the cleavage of fibronectin type III domain-containing 5. Irisin regulates mitochondrial energy, glucose metabolism, fatty acid oxidation, and fat browning. Skeletal muscle and cardiomyocytes produce irisin and affect various cardiovascular functions. In the early phase of acute myocardial infarction, an increasing irisin level can reduce endothelial damage by inhibiting inflammation and oxidative stress. By contrast, higher levels of irisin in the later phase of myocardial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…Myocardial dysfunction is an important feature of cardiomyopathy caused by many reasons. Myocardial dysfunction eventually leads to heart failure (HF) [ 1 ]. Genetic factors are also a key factor in the occurrence of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial dysfunction is an important feature of cardiomyopathy caused by many reasons. Myocardial dysfunction eventually leads to heart failure (HF) [ 1 ]. Genetic factors are also a key factor in the occurrence of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…A selective patient population, such as those with cachexia, T2DM, or chronic kidney disease [ 36 , 37 , 38 ], also presents challenges in this regard. On this occasion, irisin was a promising indicator of CV events [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…M. Y. Ho and C. Y. Wang (2021) identified the mechanisms of action of irisin through the main pathways PI3K / Akt / eNOS, AMPK [6]. Authors G. Zhu et al (2016) found that irisin not only directly regulates the number of endothelial progenitor cells, but can also act indirectly by regulating glucose and triglyceride metabolism [23].…”
Section: Discussionmentioning
confidence: 99%